The effectiveness of active recovery (jogging and cycling) post-football match simulation on athletes' heart rate and fatigue levels - Akbar, Muhammad; Dwi Marhaendro, Agus Susworo; Dharma Hita, I Putu Agus; Ariestika, Elsa (Universitas Nusantara PGRI Kediri, 2021)
Active recovery is recommended to help the soccer player recover quickly. However, there has been no study comparing the most effective active recovery methods post-match. The purpose of this study was to compare active recovery (jogging and cycling) to the heart rate and fatigue level of athletes. This study uses an experimental method with a pretest-posttest crossover design approach. Subjects were 22 male amateur football athletes with an average (age, 19.40 ± 1.18 years; height, 170.04 ± 3.54 cm; weight, 62.89 ± 5.44 kg). The results showed that the average heart rate (HR), vertical jump (VJ), and lactate levels between groups after the simulation match did not show significant differences (HR p= 0.748, VJ p=0.984, lactate p=0.633). However, for variables HR and lactate levels experienced a significant decrease after undergoing recovery treatment, and when viewed from the delta the jogging group experienced a decrease (HR 24.7%, and lactate 52.5%), for the bicycle group (HR 29.3%, and lactate 60.9%) and the sitting group (HR 19.91%, and lactate 23.4%). So the results of this study provide evidence that post-match cycling can contribute to a more effective active recovery strategy. Thus the results of this study can be used as a reference for coaches and athletes in a good recovery process after a football match.